Functional benefits of predator species diversity depend on prey identity - Wilby, A.; Villareal, S.C.; Lan, L.P.; Heong, K.L.; Thomas, M.B. (Wiley, 2005)
1. Determining the functional significance of species diversity in natural enemy assemblages is a key step towards prediction of the likely impact of biodiversity loss on natural pest control processes. While the biological control literature contains examples in which increased natural enemy diversity hinders pest control, other studies have highlighted mechanisms where pest suppression is promoted by increased enemy diversity.2. This study aimed to test whether increased predator species diversity results in higher rates of predation on two key, but contrasting, insect pest species commonly found in the rice ecosystems of south‐east Asia.3. Glasshouse experiments were undertaken in which four life stages of a planthopper (Nilaparvata lugens) and a moth (Marasmia patnalis) were caged with single or three‐species combinations of generalist predators.4. Generally, predation rates of the three‐species assemblages exceeded expectation when attackingM. patnalis, but not when attackingN. lugens.In addition, a positive effect of increased predator species richness on overall predation rate was found withM. patnalisbut not withN. lugens.5. The results are consistent with theoretical predictions that morphological and behavioural differentiation among prey life stages promotes functional complementarity among predator species. This indicates that emergent species diversity effects in natural enemy assemblages are context dependent; they depend not only on the characteristics of the predators species, but on the identity of the species on which they prey.